The Clinical Utility and Cost of Postoperative Mammography Completed within One Year of Breast Conserving Therapy: Is it Worth It?. Issue 8 (August 2017) - Allen, Ahkeel; Cauthen, Allison; Vaughan, Justin; Dale, Paul
Breast conserving therapy (BCT), lumpectomy followed by radiotherapy, is an effective treatment for a majority of breast cancers. According to the National Comprehensive Cancer Network, mammographic imaging should be completed at least six months after completion of radiation. This study evaluates the clinical significance and financial cost of postoperative breast imaging within one year of BCT. Patients treated with BCT between 2014 and 2016 at an academic center were identified retrospectively. The medical records were reviewed to identify the timing and type of the first imaging study after BCT. This study evaluated the clinical significance and the cost of postoperative imaging. A total of 128 patients were included into the study. Seventy-six patients received mammograms 3 to 12 months after BCT. Six of the 76 postoperative mammograms required additional imaging/intervention for a total of seven additional imaging studies and three procedures, all of which revealed benign findings. None of these patients had physical examination findings that were of clinical concern. The total cost of postoperative imaging and procedures performed less than a year after BCT was estimated to be $32, 506. Postoperative imaging performed on breast cancer patients less than a year after BCT proved to be of no medical benefit and revealed no additional significant pathology. The mammographic surveillance in this study did not lead to the diagnosis of recurrent malignancy or second primary lesions and placed additional financial burden on the patient population. This study demonstrates that breast imaging within a year after BCT had no clinical impact and resulted in increased cost of care.